Virtual mode of disseminating oil palm technologies duringCovid-19 – An Appraisal: Virtual mode of disseminating oil palm technologies duringCovid-19 – An Appraisal - K L MARY RANI; M V PRASAD; R K MATHUR (Journal of Oilseeds Research, 2023)
Development of oil palm across the country necessitates organizing capacity building programmes on oil palm which is taken up regularly by ICAR-IIOPR. During Covid-19 pandemic situation ICAR-IIOPR opted for online mode for disseminating oil palm technologies. ICAR-IIOPR had organized 13 virtual trainings to about 632 officers during 2020-2022. Feedback of IIOPR virtual trainings was collected from the participants by using standardized questionnaire and data was compiled and statistical tools such as frequencies and percentages were used to know the results and draw inferences. Data was tabulated for parameters viz., devices used, interaction, virtual communication, time management etc. and it was found that 45.16 % trainees expressed that their overall feeling about IIOPR virtual trainings was good.